Mirroring universalism in Kazi Nazrul Islam: a humaniterian poet with distinctive style - Sharmily, Nawshin (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2019.